(untitled) (International conference on multidisciplinary science, 2026)
Modern methods of ultrasound diagnostics play an important role in the detection and differential diagnosis of focal pathologies of the thyroid gland. Ultrasonography is a minimally invasive, inexpensive and highly informative first-stage diagnostic method. Modern ultrasound diagnostics technologies allow us to detect structural changes in the thyroid gland and assess the risk of malignancy. Under focal pathology of the thyroid gland, we understand the presence of formations in the gland that differ in structure from the tissue. Focal pathology of the thyroid gland occurs in 4-20% of cases in adults, and in 0.2-1.5% of cases in children. When examined by palpation, nodular formations are detected in almost 5% of healthy people. The composition of focal pathology of the thyroid gland includes benign nodules and cysts, adenomas, and malignant tumors.